Lean Mining Analysis in Gold Mining Use Waste Assessment Model - Indriyani, Liga; Singgih, Moses Laksono (IPTEK Journal of Proceedings Series, 2020)
This research identifies non-value added activities and minimizes waste in the production process at a gold mine. Problems that occur include the presence of waste defects in the form of choke ore materials, mismatches in dore bullion printing, and equipment damage. Then the waste waiting caused by low-level bin ore and the presence of ponding during leaching. In addition, there is also waste over processing in the form of carbon regeneration and transportation processes in the form of altered and distant ore transportation distances. The occurrence of waste can be reduced/eliminated using the Lean Mining approach which is a method to streamline the process by eliminating/reducing the presence of waste in the mining process. Identify waste using the Waste Assessment Model (WAM) tools. The results of the analysis show that the highest waste rating is a defect, motion, waiting, and process with successive percentages of the largest i.e. 20.75%, 18.42%, 17.57%, and 14.36%. From these results then recommendations for improvements that can be proposed are controlling the size and composition of ore-sized mixtures, increasing the efficiency of the crusher using TPM analysis, optimizing maintenance, making machines/systems automatically filling gold solutions, and making standardized work